(untitled) (Fisioterapia e Pesquisa, 1995)
Bone Marrow Transplantation (BMT) is an alternative treatment for onco-haematologic diseases, perhaps it is not preclude risck factors for antigenic marrow. Graft-versus-Host disease is the more often complication after BMT. The locomotor system can be severely damaged expressing pain, muscles and bone mass decrease and functional changes. This research purpose to evaluate and propose systematized physical therapy treatment and functional rehabilitation for patients who underwent BMT and developed chronic GVHD. Took part in this search 13 patients (10 males and 3 females) mean age 24 years old (7-49 years) with diagnosis of chronic myelogenous leukemia (n=6), aplastic anemia (n=6) and myelodisplasic syndrome (n=l), who underwent BMT at University of São Paulo Medical School Clinics Hospital. They recieved physical therapy treatment once a week, based on kinesiotherapy proceedings, focusing on muscles stretching and segments mobilization. The parameters of sintomatology of pain and weakness, ROM, functional capabilities and posture evaluation were controlled. A single subjects outlining was used, comparing the acomplishment before and after physical therapy treatment. Patients who underwent BMT with restrictions of ROM, limiting posture changes, pain, fatigue, muscular weakness and dificulties in the functional capabilities were discovered in our evaluation They have Skin chronic GVHD with intense scleroderma and severe restrictions of ROM (n=l); avascular necrosis of femoral head (n=3); limiting posture changes (n=3); functional capabilities exposure with dificulties in standing up, walking and especule activities (n=6); diffused and local pain (n=6); changes related to joint hip (n=3) and severe schiatic pain (n=2); restrictions of ROM joint hip (n=4). It was observed that muscles streatchig provided an improvement of posture and functional capabilities, pain decrease and a ROM increase. We understand that physical therapy was efficient in all these aspects specially when providing these patients with a better quality of life.